Environmental Accounting and Corporate Disclosure: Global Research Trends and Conceptual Clusters - Fridatien, Ericke; Puspita, Annisa Sila; Ammar, Marah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
This study provides a bibliometric review based on 1,891 Scopus-indexed records to integrate the trends and conceptual framework discussed in environmental accounting and corporate disclosure research. The results show intensive research growth since 2015, mainly led by Chinese, American, and Australian authors. Three categories were generated through thematic analysis: environmental strategies, corporate social responsibility, and accountability modes. Environmental accounting has developed from reporting to a strategic management tool, which is closely related to corporate governance, reputation, and sustainability performance. Additional findings show that the strength of international collaboration networks has increased over time, especially with Chinese and European institutions, reflecting a trend towards increasingly globalized research collaboratives. The keyword co-occurrence map indicates a shift in research priorities, from early attention to environmental cost accounting to the latest emphasis on climate-related disclosure, ESG integration, and low-carbon transition strategies. It also shows an increasing academic focus on regulatory drivers, including IFRS S2, the EU CSRD, and national emission policies. The cross-cluster comparison of differences implies a growing similarity in environmental responsibility accounting, corporate strategy, and stakeholder expectations, which underlines a move towards more consistent and decision-useful sustainability reporting systems.